Investigation of electrical tree stress using colour techniques - Abderrazzaq, Mohammad (Universitas Muhammadiyah Surakarta, 2022)
Treeing is one of the severe problems which cause the deterioration and breakdown of electrical insulation materials. Different approaches have been used to characterise this phenomenon, from experiments to analysis. The results of both methods were criticised for their dependence on the assumptions and applied conditions. In this work, the role of colours in understanding the characteristics of electrical treeing in composite insulation was employed. The relationship between the induced strain, associated with the electrical tree, and the change of colour parameters, represented by hue, saturation, and value indicators, was presented. The images were created by relative retardation orthogonal components of the polarised white light used to illuminate the specimens in the microscope. An image-editing software was used to analyse the tree colours, whereas the MATLAB program was written to determine the colour mapping of examined image. The variation of each colour parameter was linked with the tree distribution. It was then introduced as an indicator of stress at each examined point. Therefore, the contribution of the present paper is summarised as an introduction of a new tool to characterise stress in insulation materials by converting a treed image into a numerical array of data without the need to follow a complex mathematical procedure. Finally, this paper can better assess the treeing phenomenon by correlating the direction of tree growth to the rate of change for each colour parameter in that direction.